2009
DOI: 10.1073/pnas.0811984106
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur cycling and methanogenesis primarily drive microbial colonization of the highly sulfidic Urania deep hypersaline basin

Abstract: Urania basin in the deep Mediterranean Sea houses a lake that is >100 m deep, devoid of oxygen, 6 times more saline than seawater, and has very high levels of methane and particularly sulfide (up to 16 mM), making it among the most sulfidic water bodies on Earth. Along the depth profile there are 2 chemoclines, a steep one with the overlying oxic seawater, and another between anoxic brines of different density, where gradients of salinity, electron donors and acceptors occur. To identify and differentiate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
155
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(168 citation statements)
references
References 36 publications
(52 reference statements)
11
155
0
1
Order By: Relevance
“…We recovered signatures of Mediterranean Sea Brine Lake (MSBL) groups MSBL-2 and MSBL-8 (affiliated with Spirochaetes), MSBL-5 (affiliated with Chloroflexi), MSBL-6 (affiliated with Fusobacteria), MSBL-9 (affiliated with Planctomycetes) and MSBL-7 (affiliated with Deltaproteobacteria) from both interface layers, whereas MSBL-3 (affiliated with Lentisphaerae) signatures were only detected in the UI. Archaeal and bacterial rRNA profiles are generally consistent with previous studies Borin et al, 2009;La Cono et al, 2011), although there were some differences, including the low abundance of epsilonproteobacterial and Candidate Division KB1 signatures in our study. This may be attributed to differences in methodologies applied.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We recovered signatures of Mediterranean Sea Brine Lake (MSBL) groups MSBL-2 and MSBL-8 (affiliated with Spirochaetes), MSBL-5 (affiliated with Chloroflexi), MSBL-6 (affiliated with Fusobacteria), MSBL-9 (affiliated with Planctomycetes) and MSBL-7 (affiliated with Deltaproteobacteria) from both interface layers, whereas MSBL-3 (affiliated with Lentisphaerae) signatures were only detected in the UI. Archaeal and bacterial rRNA profiles are generally consistent with previous studies Borin et al, 2009;La Cono et al, 2011), although there were some differences, including the low abundance of epsilonproteobacterial and Candidate Division KB1 signatures in our study. This may be attributed to differences in methodologies applied.…”
Section: Resultssupporting
confidence: 90%
“…Studies of Discovery, L'Atalante, Urania, Thetis and Bannock basins revealed that DHAB interfaces harbor abundant and diverse microbial communities that include numerous novel candidate divisions that are more productive than most pelagic marine systems (see, for example, Sass et al, 2001;Van Der Wielen et al, 2005;Yakimov et al, 2007;Edgcomb et al, 2009;Stock et al, 2012). Functional analyses of these communities based on PCR amplification of key functional genes as well as activity measurements revealed sulfur cycling and methanogenesis to be dominant prokaryotic metabolic processes supporting life in DHABs and contributing to observed elevated biomass in DHAB haloclines (Daffonchio et al, 2006;Yakimov et al, 2007;Borin et al, 2009). Recent advances in RNA isolation, amplification and high-throughput sequencing make it possible to acquire millions of sequences of transcribed genes from microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, microbial life from all three domains has been shown to occur in such aquatic systems (e.g. van der Wielen et al 2005;Daffonchio et al 2006;Alexander et al 2009;Borin et al 2009;Yakimov et al 2007a). While new cell morphologies and ecophysiological traits have been assigned to some of these microorganisms, only recently a more specific picture of the metabolic activities of DHAB microorganisms has started to emerge, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While new cell morphologies and ecophysiological traits have been assigned to some of these microorganisms, only recently a more specific picture of the metabolic activities of DHAB microorganisms has started to emerge, e.g. S--oxidizing chemolithotrophy, microaerophilic autotrophy, heterotrophic sulfate reduction, methanogenesis and anaerobic methane oxidation (Borin et al 2009;La Cono et al 2011;Ferrer et al 2012;Pachiadaki et al 2014;Yakimov et al 2013;Alcaide et al 2015). In spite of these recent advances, we still know little about how these microorganisms survive and grow under the prevailing conditions of the DHABs.…”
Section: Introductionmentioning
confidence: 99%
“…It may possibly occur when such proteins of these organisms shared for energetic metabolisms in a microbial consortium (Lee et al 2008;Henderson et al 2010). AroB family of methanogens has phylogenetically corresponded with sulfur utilizing archaea as a result of sulfur cycling and methanogenesis are primarily drive microbial colonization (Borin et al 2009). Hence, it revealed the phylogenetic and metabolic relatedness for heavy metal assimilation pathways can likely be established among methanogens, sulfur utilizing archaea and methylotrophs, which is agreed with earlier works (Boetius et al 2000;Thomsen et al 2001;Orphan et al 2001Orphan et al , 2003Teske et al 2003;Caldwell et al 2008).…”
Section: Discussionmentioning
confidence: 99%